Wastewater treatment plant in Villapinzon (2021)
This research allows us to analyze the social, ecological and economic problems caused by the recovery of contaminated water with the implementation of the Wastewater Treatment Plant (WWTP), in the municipality of Villapinzón, where the Bogotá River is born, in order to mitigate the effects generated by the high levels of contamination of the river, as a benefit for the inhabitants of the upper basin, who are supplied by the ecosystem services of the tributary on the Páramo de Guacheneque, whose water quality has been threatened by all kinds of discharges, garbage, waste and sewage as a consequence of agricultural and industrial activities.